An Overview of Extracellular Matrix-Based Bioinks for 3D Bioprinting - Wang, Haonan; Yu, Huaqing; Zhou, Xia; Zhang, Jilong; Zhou, Hongrui; Hao, Haitong; Ding, Lina; Li, Huiying; Gu, Yanru; Ma, Junchi; Qiu, Jianfeng; Ma, Depeng (Frontiers in Bioengineering and Biotechnology, 2022)
As a microenvironment where cells reside, the extracellular matrix (ECM) has a complex network structure and appropriate mechanical properties to provide structural and biochemical support for the surrounding cells. In tissue engineering, the ECM and its derivatives can mitigate foreign body responses by presenting ECM molecules at the interface between materials and tissues. With the widespread application of three-dimensional (3D) bioprinting, the use of the ECM and its derivative bioinks for 3D bioprinting to replicate biomimetic and complex tissue structures has become an innovative and successful strategy in medical fields. In this review, we summarize the significance and recent progress of ECM-based biomaterials in 3D bioprinting. Then, we discuss the most relevant applications of ECM-based biomaterials in 3D bioprinting, such as tissue regeneration and cancer research. Furthermore, we present the status of ECM-based biomaterials in current research and discuss future development prospects.